2006
DOI: 10.15388/na.2006.11.4.14737
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of the Combined Free-Forced Convection and Mass Transfer Flow Past a Vertical Porous Plate in a Porous Medium with Heat Generation and Thermal Diffusion

Abstract: The problem of combined free-forced convection and mass transfer flow over a vertical porous flat plate, in presence of heat generation and thermaldiffusion, is studied numerically. The non-linear partial differential equations and their boundary conditions, describing the problem under consideration, are transformed into a system of ordinary differential equations by using usual similarity transformations. This system is solved numerically by applying Nachtsheim-Swigert shooting iteration technique together w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…Ali and Yousef [9] considered the problem of laminar mixed convection from a continuously moving vertical plate with suction/injection. Similar flow situations were studied for micropolar fluids by Gorla et al [10,11] and for surface embedded in porous medium by Alam et al [12]. In all these papers, the velocity and thermal boundary layer for the case of constant surface temperature or variable temperature and heat flux at the surface have been considered.…”
Section: Introductionmentioning
confidence: 90%
“…Ali and Yousef [9] considered the problem of laminar mixed convection from a continuously moving vertical plate with suction/injection. Similar flow situations were studied for micropolar fluids by Gorla et al [10,11] and for surface embedded in porous medium by Alam et al [12]. In all these papers, the velocity and thermal boundary layer for the case of constant surface temperature or variable temperature and heat flux at the surface have been considered.…”
Section: Introductionmentioning
confidence: 90%
“…The system of non-linear and locally similar ordinary differential equations (26)- (28) together with the boundary conditions (23) have been solved numerically by using Nachtsheim-Swigert shooting iteration technique [37] along with sixth order Runge-Kutta integration scheme. The detailed discussion of the method can be found in our earlier paper Alam et al [34]. Thus adopting this numerical technique, a computer program was set up for the solutions of the governing non-linear partial differential equations of our problem where the integration technique was adopted as a sixth-order Runge-Kutta method of integration.…”
Section: Methods Of Numerical Solutionmentioning
confidence: 99%
“…x H be the x-component induced magnetic field; σ is the electrical conductivity; κ is thermal conductivity; p c is the specific heat at the constant pressure and w H is the induced magnetic field at the wall. Since the solutions of the governing Equations (16) to (19) under the initial (20) and boundary (21) conditions will be based on the finite difference method it is required to make the said equations dimensionless [27]. After introducing the dimensionless quantities and proper simplifications we obtain the following nonlinear coupled partial differential equations in terms of dimensionless variables,…”
Section: Mathematical Formulationsmentioning
confidence: 99%
“…Recently both Soret and Dufour effects on steady mixed convection flow past a semi-infinite vertical porous flat plate in a porous medium with variable suction was investigated by Alam and Rahman [18]. Quite recently Alam et al [19] studied Numerical Study of the Combined Free-Forced Convection and Mass Transfer Flow Past a Vertical Porous Medium with Heat Generation and Thermal Diffusion. Very recently, a number of studies of unsteady heat transfer boundary layer flow were reported in the literature [20]- [26].…”
mentioning
confidence: 99%